The Pronunciation Learning Strategies Among Adult ESL Learners In A College - binti Long Tuan Kechik, Tuan Siti Mastazameatun (Jurnal KIAS, 2013)
This research is conducted to examine the strategies used in the process of learning English pronunciation among adult learners in a college. A sample of 50 respondents was selected randomly from among the diploma students at Sultan Ismail Petra International Islamie College (KIAS), Nilam Puri, Kota Bharu, Kelantan. All data are collected through a Likert scale questionnaire as the research instrument. It is then analyzed using SPSS version 7.0 software for statistical analysis Data analysis shows that gender has influenced the selection of learning strategies and attitudes towards English subject. However, the use of all learning strategies that are recommended in the study is comprehensive in which all students are being involved in all learning processer as proposed through Kolb's Learning Cycle. Moreover, the attitude of an adult student who studies English pronunciation is not affected by the level of skills in listening, speaking, writing and reading. Finally, data analysis shows no significant correlation between English language pronunciation learning strategies with learners attitudes towards learning English pronunciation.